Developing civil competences through a socially responsible course - Erika Zuta; Alonso Velasco; Johanna Rodriguez (Pontificia Universidad Católica del Perú, 2014)
The objective of the following article is to demonstrate the importance of giving classes about the human rights of children and teenagers at public educational institutions, given that this aspect is included in legal education and lies in the context of the Project Curso socialmente responsable (Socially responsible course).This project was awarded a sum of money or fund (Fondo Concursable para docentes), which was for a group of teachers that belong to the Academic Council of Social Responsibility (DARS) at the Pontificia Universidad Católica del Perú (PUCP). The aim of this project was to bring together the students of both the course of Social Awareness or Prosode (Faculty of Law-PUCP) and Didactics of Social Sciences (Faculty of Education- PUCP), and give them the opportunity to share their ideas/perceptions about the responsibility of the university.